Performance enhancement of gas cyclone with streamlined ports using CFD simulations - Moustafa M. Soliman; Yasser El-shaer; Khairy Elsayed; Mohamed A. Ibrahim (Journal of Engineering and Applied Science)
Abstract Cyclones are extensively utilized as gas-solid separators in many industries such as pharmaceuticals, food processing, and powder handling often use mini cyclones for efficient dust collection, air filtration, and contaminant separation in compact systems. The impact of the cyclone vortex finder (VF) diameter, the VF inlet bell mouth shape, and the VF inlet curvature on both flow field distribution and performance has been analyzed through computational analysis employing the Reynolds stress turbulence model (RSM) for twelve cyclone separators. The results demonstrate that decreasing the diameter of the VF by 33% elevates the ultimate tangential velocity by 66%. The ultimate tangential velocity nearly reaches four times the inlet velocity. A reduction of 14% in the VF inlet curvature results in a 6% enlarging in the pressure loss. Enhancing the bell mouth configuration of the inlet VF by 25% decreases the maximum pressure by 3.7%. Increasing the diameter of the VF, the VF inlet curvature, and the VF inlet bell mouth shape will also lead to reduced $${x}_{50}$$ x 50 . The cyclone with no curvature exhibits lower pressure and tangential velocity compared to the cyclones with curvature and radius of bell mouth shape of (DX/D) ratio equal 0.5. However, all the three cyclones have the same ratio. Cyclones A0 and C1 have the highest collection efficiency of all cyclone models.